High-throughput surface-enhanced Raman scattering sensors for near-infrared detection of biochemical molecules - Wang, Yifan (2023)
The inappropriate usage of biochemical molecules has led to serious environmental problems, and there is an urgent need to seek low-cost biochemical molecular sensors. Surface-enhanced Raman scattering (SERS) has received extensive attention due to their high sensitivity and specificity but is limited by low utilization and high cost. Here, we develop a high-throughput and highly sensitive NIR-SERS biochemical sensor (HNIR-SERS sensor) by combining inkjet printing technology with plasmonic metallic nanoparticles. First, we fabricated gridded substrates using imprinting technology, where the separated areas are in a typical cubic arrangement. Porous Au@AuAg yolk-shell nanorods (NRs), serving as assembly units, were then regularly assembled on the substrates by inkjet printing, forming an HNIR-SERS sensor. This new kind of HNIR-SERS sensor can achieve high sensitivity detection of multi biochemical molecules in one sensor substrate. As an example, this HNIR-SERS sensor enables efficient detection of 4-aminothiophenol (4-ATP) and rhodamine 6G (R6G), with an enhancement factor (EF) of 108 for 4-ATP. This work provides an effective method to achieve high-throughput and low-cost NIR-SERS sensors for pushing the practical application in Raman detection chips.